Chronic exogenous corticosterone administration generates an insulin-resistant brain state in rats - Osmanovic, Jelena; Plaschke, Konstanze; Salkovic-Petrisic, Melita; Grünblatt, Edna; Riederer, Peter; Hoyer, Siegfried (Stress, 2010)
We investigated whether long-term administration of exogenous corticosterone (CST) or vehicle as daily treatment induces changes in rat behavior and in gene expression of the rat brain insulin signaling pathway and the formation of tau protein. Two groups of male adult rats received daily subcutaneous injections of 26.8 mg/kg CST (CST stress group) or vehicle-sesame oil (injection stress group) for 60 days while the third group was taken as untreated controls (n = 8 each). Body weight and plasma CST were measured and psychometric investigations were conducted using a rat holeboard test system before and after the treatment. Gene expression analyzes were performed by RT-PCR in cerebral cortical tissue for insulin genes 1 and 2, insulin receptor (IR), insulin degrading enzyme (IDE), and tau protein. Daily injections of CST for 60 days induced a significant, 2-fold increase in rat plasma CST concentrations in comparison to untreated controls. Significantly reduced behavioral abilities in CST-treated rats were associated with reduced gene expression of insulin 1 ( − 20%), IDE ( − 23%), and IR ( − 26%), indicating an insulin-resistant brain state, followed by increased tau protein (+28%) gene expression. In summary, chronic CST administration affects gene expression in the brain IR signaling cascade and increases tau gene expression, which is associated with reductions in cognition capacity in rats.